Green manufacturing practices (GMP) framework for local small and medium enterprises (SME) in Johor, Malaysia: a review on enablers and barriers and preliminary findings on critical factors - Zakaria, Nur Syuhada; Haji Hasan, Sulaiman (Engg Journals Publications, 2017)
This study focuses mainly on Green Manufacturing Practices (GMP) for local small medium enterprises (SME) in the state of Johor, Malaysia. This review includes the enablers and barriers in GMP from previous studies in local and international contexts. Critical factors that affect GMP were also highlighted. It also points out relationships between enablers and barriers of GMP and measures the strengths and weaknesses of GMP. This paper also reviewed the implementation practices, issues and norms. The reviewed outcome will be a guide to formulate an effective framework for GMP in SME.